2021
DOI: 10.1161/circresaha.120.318458
|View full text |Cite
|
Sign up to set email alerts
|

Innervation and Neuronal Control of the Mammalian Sinoatrial Node a Comprehensive Atlas

Abstract: Rationale: Cardiac function is under exquisite intrinsic cardiac neural control. Neuroablative techniques to modulate control of cardiac function are currently being studied in patients, albeit with variable and sometimes deleterious results. Objective: Recognizing the major gaps in our understanding of cardiac neural control, we sought to evaluate neural regulation of impulse initiation in the sinoatrial node as an initial discovery step. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 94 publications
4
53
0
Order By: Relevance
“… 47 , 48 This disparity between in vivo and isolated single cell firing rates reflects strong input from the sympathetic arm of the autonomic nervous system, which increases firing rate through the activation of cAMP/protein kinase A signaling. Indeed, recent studies by Brennan et al 23 and Hanna et al 49 suggested that sympathetic innervation and drive is larger in the superior compared with the inferior SAN. Thus, a combination of higher AP firing, Ca 2+ cycling, and contraction rates as well as cAMP production may conspire to produce a much larger energetic load in superior than inferior SAN myocytes.…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 This disparity between in vivo and isolated single cell firing rates reflects strong input from the sympathetic arm of the autonomic nervous system, which increases firing rate through the activation of cAMP/protein kinase A signaling. Indeed, recent studies by Brennan et al 23 and Hanna et al 49 suggested that sympathetic innervation and drive is larger in the superior compared with the inferior SAN. Thus, a combination of higher AP firing, Ca 2+ cycling, and contraction rates as well as cAMP production may conspire to produce a much larger energetic load in superior than inferior SAN myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study provides the data needed to begin a modeling effort focused on neuroanatomical and electrophysiological properties of the intrinsic cardiac neurons. Integrating these findings with other data obtained from our collaborative SPARC consortium will enable development of computational models of neurons and networks in the RAGP as a critical mediator of vagal control of the heart (Hanna et al, 2021). With the RAGP as a starting point, the RAGP network model can be further expanded into a systems model of autonomic control of cardiovascular function to test novel control strategies for neuromodulation and to open the door to more effective therapeutics.…”
Section: Access Isciencementioning
confidence: 97%
“…We now find consistent neuroanatomical structure and diverse molecular properties of ganglia in the ICNS of a large porcine mammal, accepted as close to human. Our newly developed data demonstrate that the local cardiac ganglia harbor anatomical and molecular features necessary to function as complex signal processing units that critically mediate vagal control of heart function and health (Hanna et al, 2021).…”
Section: Access Isciencementioning
confidence: 98%
See 1 more Smart Citation
“…The ICNS neurons utilize a variety of neurotransmitters and modulators and receive the inputs of both local afferent and extrinsic autonomic (parasympathetic and sympathetic) nerves, performing very complicated integration in controlling cardiac functions ( Achanta et al., 2020 ; Ardell and Armour, 2016 ; Hanna et al., 2021 ; Moss et al., 2021 ). We previously identified multiple clusters of ICNS neurons on the epicardium of the superior surface of the heart and on the posterior left atrium ( Achanta et al., 2020 ; Ai et al., 2007 ; Cheng et al., 1999 ; Lin et al., 2008 ; Pauza et al., 2000 ; Richardson et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%